2023
DOI: 10.3390/ijms242317042
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Neutrophils with the Polymeric Molecular Components of the Biofilm Matrix in the Context of Implant-Associated Bone and Joint Infections

Davide Campoccia,
Stefano Ravaioli,
Rasoul Mirzaei
et al.

Abstract: In the presence of orthopedic implants, opportunistic pathogens can easily colonize the biomaterial surfaces, forming protective biofilms. Life in biofilm is a central pathogenetic mechanism enabling bacteria to elude the host immune response and survive conventional medical treatments. The formation of mature biofilms is universally recognized as the main cause of septic prosthetic failures. Neutrophils are the first leukocytes to be recruited at the site of infection. They are highly efficient in detecting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…The extracellular polymeric substance (EPS) of the biofilm is mainly composed of polysaccharides, proteins, teichoic acids, and extracellular DNA. [10,27]. The principal polysaccharide is the Polysaccharide Intercellular Adhesin (PIA), a linear homoglycan composed of β-1,6-linked N-acetylglucosamine residues.…”
Section: How Staphylococci Escape Host Defenses and Antibiotics In Pe...mentioning
confidence: 99%
See 2 more Smart Citations
“…The extracellular polymeric substance (EPS) of the biofilm is mainly composed of polysaccharides, proteins, teichoic acids, and extracellular DNA. [10,27]. The principal polysaccharide is the Polysaccharide Intercellular Adhesin (PIA), a linear homoglycan composed of β-1,6-linked N-acetylglucosamine residues.…”
Section: How Staphylococci Escape Host Defenses and Antibiotics In Pe...mentioning
confidence: 99%
“…eDNA strengthens the biofilm, acts as a gene pool for horizontal gene transfer, serves as a source of nutrients, and prevents phagocytosis [43,46,47]. Moreover, eDNA contributes to the complex architecture of the bacterial biofilm matrix through a variety of interactions with other molecular components of the biofilm matrix [27,46].…”
Section: How Staphylococci Escape Host Defenses and Antibiotics In Pe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Not all of the roles of eDNA are helpful to the biofilm—it can also act as a pathogen-associated molecular pattern (PAMP). Bacterial eDNA can be recognized by the innate immune system by toll-like receptors, particularly TLR9, which is triggered upon phagocytosis of eDNA ( Knuefermann et al., 2007 ; Campoccia et al., 2023 ). One group found that the treatment of P. aeruginosa biofilms with DNase I reduced the ability of the biofilm to upregulate neutrophil activation markers and reduced the release of neutrophil proinflammatory cytokines ( Fuxman Bass et al., 2010 ).…”
Section: Other Roles Of Ednamentioning
confidence: 99%